2016
DOI: 10.1099/mic.0.000274
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical characterization of the O antigens of two Proteus strains, O8-related antigen of Proteus mirabilis 12 B-r and O2-related antigen of Proteus genomospecies 5/6 12 B-k, infecting a hospitalized patient in Poland

Abstract: A hospitalized 73-year-old woman was infected with a Proteus mirabilis strain, 12 B-r, isolated from the place of injection of a blood catheter. Another strain, 12 B-k, recognized as Proteus genomospecies 5 or 6, was isolated from the patient's faeces, which was an example of a nosocomial infection rather than an auto-infection. Serological investigation using ELISA and Western blotting showed that strain 12 B-k from faeces belonged to the Proteus O2 serogroup. Strain 12 B-r from the wound displayed cross-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…A total of the 580 S strains (possessing an O antigen in the LPS molecules) were serologically investigated to classify them into proper O serogroups in the genus Proteus. The results for 24 of these strains classi ed to O2, O8, O11, O77 -O82 serogroups, respectively, had been reported previously [13][14][15][16][17][18][19][20] .…”
Section: Serological Featuressupporting
confidence: 79%
See 4 more Smart Citations
“…A total of the 580 S strains (possessing an O antigen in the LPS molecules) were serologically investigated to classify them into proper O serogroups in the genus Proteus. The results for 24 of these strains classi ed to O2, O8, O11, O77 -O82 serogroups, respectively, had been reported previously [13][14][15][16][17][18][19][20] .…”
Section: Serological Featuressupporting
confidence: 79%
“…Other frequent sources of isolation were connected with the respiratory tract (bronchoaspirates, sputum, and the pharyngonasal cavity), faeces, and vagina, while strains from other sources were isolated rarely. Moreover, the bacteria ( ve P. mirabilis strains) were also detected in faecal samples taken from only ve out of 181 healthy volunteers (2.8%) and in faecal samples from as many as six out of eight infected individuals (four P. mirabilis, one P. vulgaris, and one P. genomospecies 5/6 including four strains reported earlier [13,14,20]). Thus, it was shown that the 11 Proteus spp.…”
Section: Physiological Featuresmentioning
confidence: 78%
See 3 more Smart Citations